Comparative nootropic effect of evolvulus alsinoides and convolvulus pluricaulis. - PREETI KOTHIYAL; M.S.M RAWAT (International Journal of Pharma and Bio Sciences, 2026)
The aim of the present study was to highlight the comparative nootropic effects of Evolvulus alsinoides and Convolvulus pluricaulis using two validated models of memory namely jumping box and elevated plus maze. Evolvulus alsinoides and Convolvulus pluricaulis are regarded as the botanical source of Shankhpushpi along with Clitorea ternatea and Canscora decussata. Shankhpushpi, an important drug of indigenous system of medicine is known as a brain tonic, alterative and laxative. However various authors on Indian medicinal plants have different opinion about its correct botanical source. Rats were treated orally with vehicle (2% Tween 80 suspension), standard treatment (Piracetam, 200mg/kg body weight), alcoholic extracts of Evolvulous alsinoides and Convolvulus pluricaulis (250mg/kg body weight) respectively, one hour prior to the evaluation of behavioral parameters. The results indicate that alcoholic extracts of Evolvulous alsinoides exhibited superior nootropic activity as compared to Convolvulus pluricaulis in terms of time spent in the enclosed arm in plus maze model and the mean avoidance response on the jumping box model